Development and validation of a population-based anatomical colorectal model for radiation dosimetry in late effects studies of survivors of childhood cancer. (November 2022) - Owens, Constance A.; Rigaud, Bastien; Ludmir, Ethan B.; Gupta, Aashish C.; Shrestha, Suman; Paulino, Arnold C.; Smith, Susan A.; Peterson, Christine B.; Kry, Stephen F.; Lee, Choonsik; Henderson, Tara O.; Armstrong, Gregory T.; et al.
Highlights: Developed a colorectal model that includes anatomical variations of 103 individuals. Colorectal model is age-scalable (0.1–18 years) across the pediatric age range. Integrated colorectal model into the age-scalable in-house phantom. The colorectal model can be integrated into any computational phantom. The colorectal model will be used for dose reconstruction in late effects studies. Abstract: Purpose: The purposes of this study were to develop and integrate a colorectal model that incorporates anatomical variations of pediatric patients into the age-scalable MD Anderson Late Effects (MDA-LE) computational phantom, and validate the model for pediatric radiation therapy (RT) dose reconstructions. Methods: Colorectal contours were manually derived from whole-body non-contrast computed tomography (CT) scans of 114 pediatric patients (age range: 2.1–21.6 years, 74 males, 40 females). One contour was used for an anatomical template, 103 for training and 10 for testing. Training contours were used to create a colorectal principal component analysis (PCA)-based statistical shape model (SSM) to extract the population's dominant deformations. The SSM was integrated into the MDA-LE phantom. Geometric accuracy was assessed between patient-specific and SSM contours using several overlap metrics. Two alternative colorectal shapes were generated using the first 17 dominant modes of the PCA-based SSM. Dosimetric accuracy was assessed by comparing colorectal doses from test patients' CT-based RT plans (ground truth) with reconstructed doses for the mean and two alternative models in age-matched MDA-LE phantoms. Results: When using all 103 PCA modes, the mean (min–max) Dice similarity coefficient, distance-to-agreement and Hausdorff distance between the patient-specific and reconstructed contours for the test patients were 0.89 (0.85–0.91), 2.1 mm (1.7–3.0), and 8.6 mm (5.7–14.3), respectively. The average percent difference between reconstructed and ground truth mean and maximum colorectal doses for the mean (alternative 1, 2) model were 6.3% (8.1%, 6.1%) and 4.4% (4.3%, 4.7%), respectively. Conclusions: We developed, validated and integrated a colorectal PCA-based SSM into the MDA-LE phantom and demonstrated its dosimetric performance for accurate pediatric RT dose reconstruction.